Research on e-Learning and ICT in Education
XXII, 316 p. 77 illus.
Keywords: An essential text for researchers and academics seeking the most comprehensive and up-to-date coverage of all aspects of ICT in education and e-learning, this book is a multidisciplinary forum covering technical, pedagogical, organizational, instructional, and policy aspects of the topic. Special emphasis is given to applied research relevant to educational practice and guided by the educational realities in schools, colleges, universities and informal learning organizations. The volume encompasses the current trends and issues which determine and inform the integration of ICT into educational practice, including teaching and learning, curriculum and instructional design, appropriate learning media and environments, teacher education and professional development, and appropriate assessment and evaluation.